Evaluation of Antidiarrheal and Nephroprotective Activities of Mastagi Romi (Pistacia lentiscus) in Experimental Rat Models - Abdul Arafath Raza K.; Syed Safiullah Ghori; Rahemeen bano; Mohammed Al Saiqali; Mohammed Fareedullah; Zaibunissa Begum (The Bioscan, 2025)
Background: Mastagi romi (Pistacia lentiscus) has been traditionally used in Unani medicine for gastrointestinal disorders and kidney ailments. However, its pharmacological effects have not been extensively evaluated using modern scientific methods. Objective: To assess the antidiarrheal and nephroprotective activities of Mastagi romi in experimental rat models. Methods: The antidiarrheal activity was evaluated using castor oil-induced diarrhea and gastrointestinal motility test models. Nephroprotective effects were assessed in a gentamicin-induced nephrotoxicity model. Mastagi romi was administered orally at doses of 102.7 mg/kg and 205.55 mg/kg, calculated based on traditional human doses. Results: In the castor oil-induced diarrhea model, Mastagi romi at 205.55 mg/kg significantly reduced diarrheal feces (p < 0.05) with 52.63% inhibition. In the gastrointestinal motility test, Mastagi romi at 102.7 mg/kg significantly decreased intestinal transit (p < 0.05) with 19% inhibition. In the nephrotoxicity model, Mastagi romi at 102.7 mg/kg significantly reduced serum urea and blood urea nitrogen levels (p < 0.05) compared to the gentamicin group. Conclusion: Mastagi romi demonstrated significant antidiarrheal and nephroprotective activities in experimental models, supporting its traditional use and potential as a therapeutic agent for gastrointestinal and renal disorders. e current analysis aids in understanding the effect of pH and temperature in growth of Fusarium oxysporum f. sp. vasinfectum (FOV). This study also focuses on incidences of Fusarium wilt disease in six places of Tamil Nadu. The isolation of the fungus was done using three different media including potato dextrose agar media, Fusarium specific medium and Czapek’s (Dox) broth. The result imparted that the fungus has higher disease incidences in thiruchencodu region 20.50%) and significant effect on the selected parameters. it emphasis that wilt disease of cotton is endemic and causes destruction to the crop. It gives us a reason to adapt to resistant varieties and integrated pest management strategies to efficiently produce disease free cotton to support the economy of our country.